Fenomena Takfiri: Aplikasi Hermeneutika Al-Qur’an Nasr Hamid Atas Surat Al-Hujurat Ayat: 11 - FATIMAH (STAI Darussalam Lampung, 2023)
Abstract This article is discussing on takfiris phenomenon that people accuse, insult, and underestimate each other both words and deeds. The phenomenon has become a disaster for Muslims. They consider themselve more superior than others and their goal is to kill their character who have different views with them by doing tahkim. Even though, al-Qur’an forbids such behaviours in the surah al-Hujarat: 11. This research uses Nashr Hamid Abu Zaid’s hermeneutic approch that try to find out original meaning (ma’na) and main message (magza). It can be concluded that takfiris phenomenon have arisen from the beginning of islamic period. The result of this research is that its original meaning surah al-Hujurat: 11 is banning people to underestimate, insult, and hate others both words and deeds. Meanwhile, the main message of the ayat is that as a human, we must respect and not to drop self esteem each other.